Optimal Destabilization of Cartels - Ludwig von Auer; Tu Anh Pham (ZBW - Leibniz Information Centre for Economics, 2020)
A model-based derivation of an effective antitrust policy requires an economic framework that includes three actors: a cartel, a group of competing fringe firms, and a welfare maximizing antitrust authority. In existing models of cartel behavior, at least one of these actors is always missing. By contrast, the present paper's oligopoly model includes all three actors. The cartel is the Stackelberg quantity leader and the fringe firms are in Cournot competition with respect to the residual demand. Taking into account that the antitrust policy instruments (effort, fine, and leniency program) are not costless for society, an optimal policy is derived.
Keywords: L13; L41; 330; antitrust; stability; Cournot fringe; oligopoly; leniency